Failure of Bloom’s learning domains in online learning: EFL learners’ perspectives - Ambalegin Ambalegin; Nurma Dhona Handayani (EduLite: Journal of English Education, Literature and Culture, 2023)
This naturalistic qualitative research investigated the insufficient performances of cognitive, affective, and psychomotor domains in online-class learning and the paradigm shifts of Bloom’s learning domains from face-to-face teaching learning process to internet-based teaching learning process. This research adapted the theory of Bloom’s taxonomy which discussed the cognitive, affective, and psychomotor domains. The data was taken by semi-structured interview with the university students about the online learning experience and the analysis was done by categorizing to get the grand theory. It was found that the online learning brought several positive sides such coming to class on time, saving cost for transportation, and paperless, and the negative sides of online learning were the limited reach, limited facilities, and over-cost of internet connection. Then, the cognitive failure in online learning affected the understanding, the affective failure in online learning affected the receiving, responding, valuing, organization, and characterization. The psycho-motoric failure in online learning affected fundamental movement, perceptual abilities, physical abilities, and skilled movement. The paradigm shift of Bloom’s learning domain is the way to teach, the way to behave, and the way to socialize.